On exact Hausdorff measure functions of operator semistable Lévy processes. Issue 6 (2nd November 2017) - Kern, Peter; Wedrich, Lina
ABSTRACT: Let X = X ( t ) t ⩾ 0 be an operator semistable Lévy process on with exponent E, where E is an invertible linear operator on . In this article, we determine exact Hausdorff measure functions for the range of X over the time interval [0, 1] under certain assumptions on the principal spectral component of E . As a byproduct, we also present Tauberian results for semistable subordinators and sharp bounds for the asymptotic behavior of the expected sojourn times of X .